Nursing teaching and the relationship between healthca-re and teaching activities in the Chilean educational and health frame - Salgado París, Jacqueline Ester; Sanhueza Alvarado, Olivia (Investigación y Educación en Enfermería, 2010)
Nursing formal education has a little more than a century in Chile and from its beginnings it was born linked to a care setting. This has generated a long data relationship between healthcare and teaching activities, implicit for all its actors but not always clear due to the absence of formal regulatory frames. The evolution of the current educational and health field politics has genera-ted change airs, ruling this existing relationship between higher education and health care institutions. This article describes the evolution of nursing teaching in its relationship between health-care and teaching activities and how the current educational and health regulatory frames could influence in the education quality and the relationship between healthcare and teaching activities.